PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAAN PELANGGAN AYAM GEPREK DI WARUNG MORRO CHICKEN KELURAHAN KAYU PUTIH KOTA KUPANG - Emiliana Sori Daiju; Lende Dangga (Jurnal Administrasi Terapan, 2025)
This study aims to examine the influence of product quality and price on customer satisfaction of Ayam Geprek at Morro Chicken, Kayu Putih Village, Kupang City. The research used a quantitative approach with an associative method. The population consisted of all Morro Chicken customers who had purchased Ayam Geprek, with a sample of 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire (1–5) and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²).The results indicate that product quality and price significantly affect customer satisfaction. Simultaneously, product quality and price have a significant effect on customer satisfaction, with an R² of 0.512, indicating that these two variables explain 51.2% of the variation in customer satisfaction. The findings emphasize that the combination of good product quality and reasonable pricing is a key factor in shaping customer satisfaction at Morro Chicken.Keywords: product quality, price, customer satisfaction, Ayam Geprek